Microfluidic sorting selects sperm for clinical use with reduced DNA damage compared to density gradient centrifugation with swim-up in split semen samples. Issue 8 (10th July 2018) - Quinn, Molly M; Jalalian, Liza; Ribeiro, Salustiano; Ona, Katherine; Demirci, Utkan; Cedars, Marcelle I; Rosen, Mitchell P
Abstract: STUDY QUESTION: Does microfluidic sorting improve the selection of sperm with lower DNA fragmentation over standard density-gradient centrifugation? SUMMARY ANSWER: Microfluidic sorting of unprocessed semen allows for the selection of clinically usable, highly motile sperm with nearly undetectable levels of DNA fragmentation. WHAT IS KNOWN ALREADY: Microfluidic devices have been explored to sort motile and morphologically normal sperm from a raw sample without centrifugation; however, it is uncertain whether DNA damage is reduced in this process. STUDY DESIGN, SIZE, DURATION: This is a blinded, controlled laboratory study of differences in standard semen analysis parameters and the DNA fragmentation index (DFI) in split samples from infertile men ( n = 70) that were discarded after routine semen analysis at an academic medical center. PARTICIPANTS/MATERIALS, SETTING, METHODS: Sperm concentration, progressive motility and forward progression were assessed by microscopic examination. For each sample, the unprocessed semen was tested for DNA fragmentation and split for processing by density-gradient centrifugation with swim-up or sorting by a microfluidic chip. DNA fragmentation was assessed in unprocessed and processed samples by sperm chromatin dispersion assay. The DFI was calculated, from up to 300 cells per slide, as the number of cells with fragmented DNA divided by the number of cells counted per slide. MAIN RESULTS AND THE ROLE OF CHANCE: The median DFI in unprocessed samples was 21% (interquartile range (IQR): 14–30). In paired analyses of all samples, those processed by the microfluidic chip demonstrated significantly decreased DFI compared to those processed by density-gradient centrifugation ( P = 0.0029) and unprocessed samples ( P < 0.0001). The median DFI for chip specimens was 0% (IQR: 0–2.4) while those processed by density-gradient centrifugation had a median DFI of 6% (IQR: 2–11). Unprocessed samples in the highest DFI quartile (DFI range: 31–40%) had a median DFI of 15% (IQR: 11–19%) after density-gradient centrifugation and DFI of 0% (IQR: 0–1.9%) after processing with the microfluidic chip ( P = 0.02). LIMITATIONS, REASONS FOR CAUTION: While a high DFI has been associated with poor outcomes with IVF/ICSI, there are limited data illustrating improvements in clinical outcomes with a reduction in DFI. As this study utilized discarded, non-clinical samples, clinical outcomes data are not available. WIDER IMPLICATIONS OF THE FINDINGS: While microfluidic sorting of unprocessed semen allowed for the selection of clinically usable, highly motile sperm with nearly undetectable levels of DNA fragmentation, standard processing by density-gradient centrifugation with swim-up did not increase DNA fragmentation in an infertile population. The proposed microfluidic technology offers a flow-free approach to sort sperm, requiring no peripheral equipment or filtration step, while minimizing hands-on time. STUDY FUNDING/COMPETING INTEREST(S): No external funding to declare. Utkan Demirci, PhD is the Co-founder and Scientific Advisor for DxNow Inc., LevitasBio Inc. and Koek Biotech. Mitchell Rosen, MD is a member of the Clinical Advisory Board for DxNow Inc.